Loyalitas Pelanggan: Digital Marketing Dan Costumer Perceived Value Terhadap Kepuasan Pelanggan Terhadap - Ismaila Tompo (STIE AMKOP, 2022)
Loyal customers are a target that must be owned by every company. This type of research is a type of quantitative research. By using a cross sectional approach. This study used the Non Probability Sampling technique by purposive sampling. With a total sample of 125 respondents. The analytical method used in this research is